Can lung function measurements be used to predict which patients will be at risk of developing interstitial pneumonitis after bone marrow transplantation?. Issue 6 (June 1992) - Milburn, H J; Prentice, H G; du Bois, R M
Abstract : BACKGROUND: Lung function often deteriorates after bone marrow transplantation for haematological malignancies. Whether pulmonary function measurements are useful for monitoring patients' progress after transplantation and for alerting clinicians to the development of pneumonitis is uncertain. METHODS: Serial pulmonary function measurements were made in 39 patients with a haematological malignancy, and the values from 18 recipients of T cell depleted allogeneic (n = 17) or autologous (n = 1) bone marrow transplants who developed interstitial pneumonitis were compared retrospectively with values from 21 recipients of allogeneic (n = 17) or autologous (n = 4) transplants who did not develop pneumonitis. Lung function was measured at the onset of a further 18 episodes of pneumonitis. RESULTS: Measurements made before transplantation showed no difference in forced expiratory volume in one second (FEV1), transfer factor for carbon monoxide (TLCO), or total lung capacity between the two groups, but the forced vital capacity (FVC) was slightly higher in those who developed pneumonitis (mean (SD)% predicted 104 (12)) than in those who did not (93 (17%)). Six weeks and three months after transplantation all pulmonary function measurements had fallen slightly in both groups but TLCO had fallen considerably more in those who later developed pneumonitis, being 71% (SD 11%) and 77% (7%) of pretransplant values in patients who later developed pneumonitis compared with 109% (38%) and 96% (26%) in those who did not. All lung function measurements were significantly lower at the onset of pneumonitis than three months after transplantation, even in patients with no abnormal signs and a normal chest radiograph. CONCLUSIONS: Serial measurements of gas transfer before and after bone marrow transplantation may be useful for predicting which patients will be at risk of developing pneumonitis and may help to diagnose pneumonitis in breathless patients with no abnormal signs.